Reinterpreting the Concept of Nusyuz of Husbands and Wives in the Perspective of Indonesian Positive Law - Winda Talita Putri winda; Dini Handayani; Sariyah (JURNAL ILMU SYARIAH, 2026)
This study examines the reinterpretation of the concept of nusyuz within the framework of Indonesian Islamic family law by analyzing both normative legal provisions and judicial practices. The issue arises from the prevailing tendency to interpret nusyuz solely as a wife’s disobedience, which often leads to unequal legal consequences and reinforces structural gender bias in the application of family law. This research aims to reassess the legal position and operational meaning of nusyuz in light of contemporary principles of justice, equality, and maqāṣid al-sharī‘ah. The study employs a normative juridical method supported by statutory, conceptual, and case approaches. Primary legal materials include Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), and relevant religious court decisions, while secondary materials consist of scholarly literature concerning Islamic family law, gender justice, and maqāṣid al-sharī‘ah. The findings reveal that nusyuz should not be understood as a concept exclusively attributed to wives but rather as a reciprocal condition that may arise from either spouse’s failure to fulfill marital obligations. The study further demonstrates that unilateral claims of nusyuz without sufficient and objective evidence are inconsistent with the principles of equality before the law and the objectives of Islamic law, which emphasize justice, human dignity, and family welfare. Therefore, a reinterpretation of nusyuz is necessary to prevent discriminatory legal outcomes and to promote a more balanced and equitable implementation of Islamic family law in Indonesia, ensuring equal legal protection for both husbands and wives within marital relationships.   Keywords: Islamic family law; legal equality; marital rights; maqāṣid al-sharī‘ah; nusyuz.